INTEGRATION OF LEARNING MODELS INTO A SOFTWARE DEVELOPMENT SYSTEM - MUNDHE VRUSHALI H; OTTENS ELIZABETH A; SRIDHAR SRIKRISHNA; BROWN ALEXANDER B; KAPOOR GAURAV; HANSON CHRISTOPHER M; SIRACUSA MICHAEL R; NATION ZACHARY A (2019)
The subject technology provides for generating machine learning (ML) model code from a ML document file, the ML document file being in a first data format, the ML document file being converted to codein an object oriented programming language different than the first data format. The subject technology further provides for receiving additional code that calls a function provided by the ML model code. The subject technology compiles the ML model code and the additional code, the compiled ML model code including object code corresponding to the compiled ML model code and the compiled additionalcode including object code corresponding to the additional code. The subject technology generates a package including the compiled ML model code and the compiled additional code. Further, the subjecttechnology sends the package to a runtime environment on a target device for execution. 本主题技术提供从机器学习(ML)文档文件生成ML模型代码，ML文档文件为第一数据格式，ML文档文件被转换为不同于第一数据格式的面向对象的编程语言的代码。本主题技术进一步提供接收调用由ML模型代码提供的函数的附加代码。本主题技术编译ML模型代码和附加代码，编译的ML模型代码包括